Existence results for impulsive neutral functional differential inclusions - Dhage, Bapurao C.; Ntouyas, Sotiris K. (Topological Methods in Nonlinear Analysis, 2005)
In this paper we prove existence results for first and second order impulsive neutral functional differential inclusions under the mixed Lipschitz and Carathéodory conditions.